The Effect of Work Stress, Work Motivation, and Work Environment on Employee Performance - Mariam Nurul Rohmah; Nugraha Saefudin (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the influence of work stress, work motivation, and work environment on employee performance at Nurul Huda Cikampek Foundation. The research background is based on the phenomenon of high work stress levels, declining motivation, and suboptimal work environment conditions at the foundation, which have contributed to decreasing employee performance over the past three years. The research employs a quantitative method with descriptive and verificative approaches. The study population includes all employees of Nurul Huda Cikampek Foundation, with a sample of 50 respondents selected using nonprobability sampling through a saturated sampling technique. Data was collected through questionnaires and analyzed using Scale Range Analysis and Path Analysis with SPSS software. The results indicate that work stress falls into the moderate category with an average score of 3.45 and has a significant negative influence on employee performance. Work motivation is in the good category with an average score of 3.82 and shows a significant positive influence. The work environment also scores well with an average of 3.60 and demonstrates a significant positive impact on performance. Partially, work stress accounts for 28.5%, work motivation for 34.2%, and work environment for 31.8% of performance variation. Simultaneous analysis reveals that these three variables collectively explain 78.6% of employee performance variance, while the remaining 21.4% is influenced by other factors beyond this study. These findings provide practical implications for the foundation's management to better manage work stress, enhance motivation, and improve work environment conditions to boost employee performance. The study also contributes to human resource management literature, particularly in the context of non-profit organizations.